Optimizing energy and thermal comfort in residential kitchens: an on-site investigation using thermal imaging - Bouthaina Sayad; Oumr Adnan Osra; Wajdy S Qattan (Journal of Asian Architecture and Building Engineering)
Residential kitchens are high-energy spaces, serving as both functional cooking areas and central zones for household energy use and thermal dynamics. This study investigates energy consumption and thermal comfort in a typical residential kitchen located in northeastern Algeria, which are high-energy-use areas with unique thermal challenges in summer. To achieve the study’s objectives, we focused on three main investigative steps. First, we assessed air temperature, humidity, and wind velocity at different points within the kitchen to identify areas with significant microclimate variation, data crucial for optimizing ventilation and cooling systems. Second, we evaluated the energy use and heat output of kitchen appliances to identify energy-intensive devices and develop strategies for reducing overall heat load. Third, we used thermal imaging to visualize heat distribution, enabling us to analyse spatial heat spread, improve heat dissipation, and reduce hotspots. The findings reveal that microclimate variations in the kitchen, influenced by cooking schedules and appliance use, create significant thermal discomfort due to heat accumulation and limited ventilation. Heat retention from envelope materials and appliances amplifies indoor temperatures, particularly in the evening. Recommendations include natural ventilation solutions, reflective materials, and thermal insulation to enhance comfort and energy efficiency.